Experiment on the separation of tail gases of ammonia plant via continuous hydrates formation with TBAB. (25th May 2015) - Sun, Qiang; Liu, Jian; Liu, Aixian; Guo, Xuqiang; Yang, Lanying; Zhang, Jingwen
Abstract: We used hydrate separation method in this paper to recover H2 and N2 from tail gases of ammonia plant in the presence of tetra-n-butylammonium bromide (TBAB). The formation condition of H2 /N2 /CH4 /TBAB hydrates was measured by pressure search method. Then the continuous separation of H2 /N2 /CH4 via hydrates formation was conducted in the presence of TBAB, and a two-stage separation process was proposed to increase the recovery of H2 and N2 . The influences of experimental pressure, temperature and gas flow on the separation results were investigated. The results show that the total concentration of H2 and N2 in the unhydrated gas (recovered gas) is 95.28 mol%, and the total recovery of H2 and N2 is more than 90%. This work supplies the preliminary ideas and fundamental data for the industrial application of hydrate separation method. Highlights: We measured the formation condition of H2 /N2 /CH4 /TBAB hydrates. We achieved continuous separation of tail gas of ammonia plant via hydrate formation. We investigated the influences of pressure, temperature and gas flow on the results. A two-stage separation process was proposed to increase the recovery of H2 and N2 .